Loss of Memo, a novel FGFR regulator, results in reduced lifespan. Issue 1 (20th September 2013) - Haenzi, Barbara; Bonny, Olivier; Masson, Régis; Lienhard, Susanne; Dey, Julien H.; Kuro‐o, Makoto; Hynes, Nancy E.
Abstract : Memo is a widely expressed 33‐kDa protein required for heregulin (HRG)‐, epidermal growth factor (EGF)‐, and fibroblast growth factor (FGF)‐induced cell motility. Studies in mouse embryonic fibroblasts, wild‐type or knockout for Memo, were performed to further investigate the role of Memo downstream of FGFR. We demonstrated that Memo associates with the FGFR signalosome and is necessary for optimal activation of signaling. To uncover Memo's physiological role, Memo conditional‐knockout mice were generated. These animals showed a reduced life span, increased insulin sensitivity, small stature, graying hair, alopecia, kyphosis, loss of subcutaneous fat, and loss of spermatozoa in the epididymis. Memo‐knockout mice also have elevated serum levels of active vitamin D, 1, 25‐dihydroxyvitamin D3 (1, 25(OH)2 D), and calcium compared to control littermates expressing Memo. In summary, the results from in vivo and in vitro models support the hypothesis that Memo is a novel regulator of FGFR signaling with a role in controlling 1, 25(OH)2 D production and normal calcium homeostasis.—Haenzi, B., Bonny, O., Masson, R., Lienhard, S., Dey, J. H., Kuro‐o, M., Hynes, N. E. Loss of Memo, a novel FGFR regulator, results in reduced lifespan. FASEB J. 28, 327–336 (2014). www.fasebj.org